The wonders : the extraordinary circus performers who transformed the Victorian age / John Woolf. - Woolf, John (Historian) (Pegasus Books, 2019)
On 23rd March, 1844, General Tom Thumb, at 25 inches tall, entered the Picture Gallery at Buckingham Palace and bowed low to Queen Victoria. On both sides of the Atlantic, this meeting marked a tipping point in the 19th century - the age of the freak was born. Bewitching all levels of society, it was a world of astonishing spectacle - of dwarfs, giants, bearded ladies, Siamese twins and swaggering showmen - and one that has since inspired countless novels, films and musicals. But the real stories, of the performing men, women and children, have been forgotten or marginalised in the histories of the very people who exploited them. In this account, Dr John Woolf uses a wealth of recently discovered material to bring to life the sometimes tragic, sometimes triumphant, always extraordinary stories of people who used their (dis)abilities and difference to become some of the first international celebrities.